Death of the patient as a burden on nurses work - Głowacka, Mariola; Haor, Beata; Ślusarz, Robert; Sołtysiak, Katarzyna; Biercewicz, Monika (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Introduction. Contact dying patients can significantly burden the nurses bio–psycho–socially. Aim. The aim of the study is to present a preliminary assessment of the extent to which the patient’s death is a burden on the practicing profession. Material and methods. A pilot study was conducted in 2011–2012 in the group of 150 nurses using a diagnostic survey, techniques, polling and survey questionnaire. Results and conclusions. Most often in a situation of death of a patient nurses felt sadness and compassion. In some respondents appeared fatigue, sleep disturbance, unwillingness to coming to work and a decrease in motivation to work. Extract the most aggravating reactions and their determinants allows the introduction of effective mitigation measures, such as workshops and psychological counseling.